Looking through Ethnoscience in Rural Areas of Jayapura: A Perspective Study in Science Learning - Budiarti, Indah Slamet; Lumbu, Albert; Boy, Bonefasius Yanwar; Wabiser, Yan Dirk (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
In rural regions, cultural practices and indigenous knowledge systems constitute valuable epistemic resources amenable to incorporation into science instruction through an ethnoscience framework. This study aimed to identify ethnoscience elements embedded within rural communities of Jayapura, Papua, Indonesia, and to examine junior high school students’ perspectives regarding the integration of such indigenous knowledge into science learning. A descriptive quantitative research design was employed. The population comprised junior high school students in rural districts of Jayapura. Through purposive sampling, 120 ninth-grade students from multiple rural schools participated. Data were collected via a validated eight-item Likert-scale questionnaire (α = 0.81) and supplemented by semi-structured interviews. Quantitative data were analyzed using descriptive statistics (frequencies, percentages, mean scores, and standard deviations), while qualitative data underwent thematic analysis. The findings revealed a significant perception gap: students demonstrated low awareness of ethnoscience as an instructional approach (M = 2.38, SD = 0.92) and limited recognition of cultural practices as scientific applications (M = 2.52, SD = 0.95). Conversely, students exhibited strong interest in environment-based science learning (M = 4.12, SD = 0.74), high perceived relevance of cultural resources for conceptual understanding (M = 4.18, SD = 0.68), and substantial willingness to learn science through cultural contexts (M = 4.22, SD = 0.65). These findings indicate that while ethnoscientific resources remain underutilized in formal instruction, students perceive considerable value in culturally contextualized science learning. The study provides empirical evidence supporting the development of culturally responsive science curricula in rural Indonesian contexts and offers practical implications for educators seeking to bridge indigenous knowledge systems with formal scientific instruction.